Seaweed as a potential source of dietary fiber - Dwiyitno Dwiyitno (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
Dietary fiber is one of the most essential food component, mainly used to maintain health andbalance of digestive system. Dietary fiber plays an important role in health, especially in reducingblood cholesterol, improving glucose absorbtion for diabetic patients, preventing colon cancer,and reducing weight. Several studies showed that seaweed is a potential source of dietary fiberwith more advantages compare to that of land-based crops. Contrary to its production, seaweedconsumption in Indonesia is relatively low. To date, dietary fiber intake for the majority of Indonesiansis fulfiled from land-based crops.